Organization of remote work in police bodies and units under martial law: managerial and ethical aspects - Lukash, Serhii; Panasiuk, Oksana; Romanov, Vitalii; Kushnir, Daria; Ponomarova, Yana; Puriha, Iryna (DIXI, 2025)
The most fundamental ethical and managerial challenges associated with organizing remote work in police agencies and units under martial law have been analyzed. It has been noted that the covid-19 pandemic was a key event that introduced new challenges to humanity while simultaneously prompting numerous organizational, managerial, and regulatory initiatives in the field of remote work. The nature of managerial decisions in this area has been clarified, and the key aspects of implementing these decisions—closely tied to the existing security situation—have been examined. Uncontrollable variables that must be considered when making managerial decisions regarding the organization of remote work in police agencies and units under martial law have also been analyzed. Additionally, the challenges and benefits of organizing professional training for police officers in a remote work environment have been explored. Regarding the ethical dimension of remote work organization in police agencies and units under martial law, the most significant ethical challenges have been identified. These challenges necessitate a fundamental reassessment of police officers’ integrity in the context of new security conditions.